Impact of the increased asylum seeker population on a UK mental health crisis service - Helen Lashwood; Mark Toynbee; Bradley Hillier; Derek Tracy (BJPsych International, 2025)
Background A large proportion of applicants for asylum in the UK are housed in contingency hotels while awaiting the outcome of their claim. As the prevalence of severe mental illness (SMI) among asylum seekers is estimated to be around 61%, a measurable impact on mental health services local to these hotels might be expected.